The Encounter between Eastern Orthodoxy and Lutheranism: A Historical and Theological Assessment - Asproulis, Nikolaos (The ecumenical review, 2017)
After the fall of the Byzantine Empire in 1453 and the following centuries of Ottoman occupation, especially in Eastern Europe and the Balkans, a series of unpredictable and difficult factors prevented Eastern Orthodoxy from engaging in a creative dialogue with the emerging Reformation of Martin Luther (1517), an event that decisively changed the course of Western history by triggering a chain of events at all levels of life. In spite of this, Luther and other Lutheran leaders initiated a continuing relationship and frank dialogue with various Orthodox churches, especially the Ecumenical Patriarchate. This encounter culminated in an official bilateral dialogue during the second half of the 20th century. In addition to the intensive formal efforts made by both traditions to find their way toward Christian unity, the long process of direct and indirect dialogue between theologians of both traditions points to a fundamental common doctrinal background shared by both church families.